Peran dan kontribusi ibn malik dalam pengembangan tata bahasa arab klasik - Khotimah, Khusnul (Maliki Interdisciplinary Journal, 2025)
This study explores the role and contribution of Imam Ibn Malik in the development of classical Arabic grammar, particularly through his monumental work, Alfiyyah Ibn Malik. As the language of the Qur’an, Arabic possesses a highly complex grammatical system, making the mastery of nahwu (syntax) and sharaf (morphology) essential in Islamic education. Ibn Malik, a prominent scholar from Andalusia who later settled in Damascus, composed the Alfiyyah, a thousand-verse didactic poem summarizing Arabic grammar rules in a concise, systematic, and memorizable form. Its poetic structure facilitated teaching and reinforced the memorization tradition in Islamic institutions and pesantren. This research employs a qualitative, biographical approach to analyze Ibn Malik’s life, works, and influence on the evolution of Arabic grammar. The findings reveal that Ibn Malik played a pivotal role not only as a compiler of rules but also as an innovative pedagogue. His contributions include synthesizing different grammatical schools (Basra, Kufa, and Baghdad) and incorporating Prophetic traditions (hadith) as linguistic evidence, a rare practice in earlier scholarship. To this day, the Alfiyyah remains central in Islamic boarding schools in Indonesia and across the Muslim world, while also being relevant to modern linguistic studies. Thus, Ibn Malik deserves recognition as a key figure in Arabic linguistic history whose influence transcends generations.